1982
DOI: 10.1152/ajpheart.1982.243.3.h351
|View full text |Cite
|
Sign up to set email alerts
|

Quantitation of changes in lymph protein concentration during lymph node transit

Abstract: Many investigators assume the protein concentration and colloid osmotic pressure of interstitial fluid and lymph to be identical even after the lymph has passed through a lymph node. We quantitated the degree of modification of lymph by the dog popliteal lymph node by perfusing isolated lymph nodes in situ at physiological flow rates with homologous plasma or plasma diluted to low protein concentration. This enabled us to compare directly prenodal and postnodal lymph flows and protein concentrations. When undi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
73
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(81 citation statements)
references
References 0 publications
6
73
1
Order By: Relevance
“…In the kidney, we found that albumin injected prenodally in a hilar lymph vessel was completely recovered in the thoracic duct (16). Since lymph node protein and fluid exchange decrease with increased flow (17), and the spleen lymph flow rates were on average ∼four times higher than that of the kidney, our kidney data suggest minimal exchange of fluid and proteins also in the spleen nodes. One way to show that spleen lymph was the dominant component in the collected lymph might have been to compare with thoracic duct lymph, which derives from the entire abdominal area (18).…”
Section: Discussionmentioning
confidence: 61%
“…In the kidney, we found that albumin injected prenodally in a hilar lymph vessel was completely recovered in the thoracic duct (16). Since lymph node protein and fluid exchange decrease with increased flow (17), and the spleen lymph flow rates were on average ∼four times higher than that of the kidney, our kidney data suggest minimal exchange of fluid and proteins also in the spleen nodes. One way to show that spleen lymph was the dominant component in the collected lymph might have been to compare with thoracic duct lymph, which derives from the entire abdominal area (18).…”
Section: Discussionmentioning
confidence: 61%
“…Such lymph-migratory DCs, exquisitely dependent upon CCR7 for their trafficking to LNs, are known to regulate the maturation of the specialized postcapillary venules in LNs, the HEVs (3, 4, 7). From this perspective, it is interesting to note that classical studies on lymphatic collecting vessels in dogs, done in vivo with LNs remaining functional during collecting vessel cannulations, show a key role for LN venules in fluid exchange and lymph flow (35)(36)(37). Specifically, the venules in LNs are responsible for uptake of water during the appreciable concentration of afferent lymph before it traverses the LN and enters efferent lymph (35).…”
Section: Animals Cx3cr1mentioning
confidence: 99%
“…6 The permeability of the collecting vessels has recently been shown to be regulated by a subset of dendritic cells. 7 Furthermore, classic studies in dogs by Adair et al 8 revealed another means by which collecting lymphatic vessel hyperpermeability develops. They observed that afferent lymph, with its typical low protein content, is filtered in the LN so that water is absorbed into the venous vasculature and efferent lymph emerges nearly as concentrated as plasma.…”
mentioning
confidence: 99%
“…They observed that afferent lymph, with its typical low protein content, is filtered in the LN so that water is absorbed into the venous vasculature and efferent lymph emerges nearly as concentrated as plasma. 8 However, increased efferent collecting vessel pressure changed the filtration properties of the LN and ultimately led to markedly leaky afferent lymphatics. 9 Lymphatic collecting vessels are surrounded by fat throughout the body.…”
mentioning
confidence: 99%